INTEGRATING SOCIAL CAPITAL INTO RURAL EMPOWERMENT: A CASE STUDY OF THE EMPOWERED VILLAGE PROGRAM IN LAMPUNG - Niik Elastiana; Luthfi Salim; Ahmad Muttaqin (Jurnal Analisa Sosiologi, 2026)
This study aims to analyze how social capital operates within rural community empowerment through the Empowered Village Program in Lampung Province, Indonesia. Although community empowerment is widely promoted, existing studies often emphasize program outputs rather than examining the mechanisms through which social capital strengthens empowerment processes, leading to limited understanding of participation dynamics and long-term sustainability. Using a qualitative descriptive case study, this research collected data over a three-month period through in-depth interviews with twelve purposively selected informants involved in program planning, implementation, and community leadership. These data were supplemented by participant observation and document analysis, with validity ensured through source triangulation, method triangulation, and member checking. The findings show that strengthening four core sectors economy, education, health, and environment enhances self-reliance, local leadership, and collective action while enabling communities to address structural barriers. The study concludes that optimizing bonding and bridging social capital is essential for sustaining empowerment and ensuring program continuity, offering practical implications for inclusive rural development